Synchrotron-radiation computed tomography of the water drop penetration time test on hydrophobic soils - Clara M. Toffoli; Marius Milatz; Julian P. Moosmann; Thomas Jentschke; Felix Beckmann; Jürgen Grabe (Journal of Rock Mechanics and Geotechnical Engineering)
The water drop penetration time (WDPT) test consists of placing water drops on a material's surface in order to evaluate how long it takes to penetrate the pores. It is used to evaluate the hydrophobicity of materials. This study aims at investigating in more detail the soil-water interaction during the test, exposing its mechanism. For that, a model soil named Hamburg Sand was coated with a hydrophobic fluoropolymer and then a WDPT test was performed while computed tomography (CT) images were taken. Tomography experiments were performed at the P07 high-energy materials science (HEMS) beamline, operated by Helmholtz–Zentrum Hereon, at the storage ring PETRA III at the Deutsches Elektronen-Synchrotron (DESY) in Hamburg. Using synchrotron radiation, a tomogram can be obtained in about 10 min, way less time than regular laboratory X-ray sources usually owned by universities. The faster imaging enables the observation of the drop penetration during time and thus provides insight into the dynamics of the process. After that, digital discrete image correlation is performed to track the displacement of the grains throughout time. From the results one can observe that, as the drop is absorbed at the material's surface, the grains directly around the droplet base are dragged to the liquid-air interface around the drop, revealing grain kinematics during capillary interactions of the penetrating liquid and sand grains.